Anti-Dislipidemia Effectiveness Test of Turmeric Ethanol Extract (Curcuma Longa) in Male Wistar Mice Given a High-Fat Diet - Wang Lei; Florenly; Liena; Fioni (Britain International for Academic Research (BIAR) Publisher, 2022)
Dyslipidemia is a condition of increasing levels of Low Density Lipoprotein (LDL), cholesterol in the blood, or triglycerides in the blood that can be accompanied by a decrease in levels of High Density Lipoprotein (HDL). Herbal products have been used since long ago in the medical world, one of which is curcuma longa root. The main compound of turmeric is curcumin which can lower cholesterol levels due to inhibiting cholesterol reabsorbtion from the outside and increase the enzyme HmgCoA reductase inhibitor so that fat synthesis can run properly. The purpose of this study was to find out the effectiveness of turmeric ethanol extract (Curcuma Longa) as an anti-dyslipidemia in male wistar rats given a high-fat diet. This experimental study with the pre-test and post-test group only control design approach was conducted in January 2021, at the Herbarium Medanese FMIPA USU. The size of the sample was calculated by Federer's formula, with at least 4 mice in each treatment group. The results and conclusions of turmeric ethanol (Curcuma Longa) III (150.20 ± 0.90 mg/dl) significantly decreased total cholesterol compared to the control group (177.50 ± 6.02mg/dl) (P value < 0.05). Turmeric ethanol extract (Curcuma Longa) III (110.00 (109-112) mg/dl) may significantly lower triglyceride levels compared to the control group (166.50 (160-175) mg/dl), (value P = 0.024). Turmeric ethanol extract (Curcuma Longa) III (66.50 ± 1.25 mg/dl) significantly lowered LDL levels compared to the control group (106.20 ± 3.50 mg/dl), (P value < 0.05). Turmeric ethanol extract (Curcuma Longa) III, (60.00 (59-61) mg/dl) can significantly increase HDL levels compared to the control group (27.00 (33-39) mg/dl), (Value P = 0.024). Turmeric ethanol extract (Curcuma Longa) III significantly lowered SGOT (Value = 0.024) and SGPT (Value P < 0.05) compared to the control group.